Condemning New Religious Streams: A Problem of Making a Civilised Umma - Nur Khalik Ridwan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
The rising of the religious sects that are claimed as deviated and infidel has been a controversial issue today. This paper reviews the phenomenon, both from the basic of Muslim’s faith and from the historical context. Based on these perspectives, this article analyzes the phenomenon of the religious sects vis a vis major groups of Islam. This phenomenon can be categorized into two perspectives; first, the sects which are claimed as deviated can be categorized as madzhab in Islam. Second, those sects can also be indicated as new religion. From the mainstream Muslim group side, the sects was not admiited both as madzhab of Islam and also new religion, because they believe that there is no true religion but Islam. Therefore, all these sects will be refused and should be destroyed. Here, Muslims are not able to make the norms of living together and harmony.In fact, Islam teaches freedom of speech, thought, and faith. Every one can choose anything without any pressure. To overcome their daily problems, they have to have sense of humanity and non-violence attitudes.Keywords: deviating, streams in Islam, problems, and civilised society